Influence of Activation Mode of Resin Cement on the Shade of Porcelain Veneers. Issue 4 (7th October 2013) - Magalhães, Ana Paula Rodrigues; Cardoso, Paula de Carvalho; de Souza, João Batista; Fonseca, Rodrigo Borges; Pires‐de‐Souza, Fernanda de Carvalho Panzeri; Lopez, Lawrence Gonzaga
Abstract Purpose The aim of this study was to evaluate the influence of resin luting cement's activation mode in the final shade of porcelain veneers after accelerated artificial aging (AAA). Materials and Methods Porcelain veneers (IPS Empress Esthetic) were produced using a standardized shade (ET1) and thickness (0.6 mm). Twenty bovine teeth were collected, prepared, and divided into two groups: group I (n = 10)—light‐cured group, only base paste was applied to the veneers; group II (n = 10)—dual‐cured group, in which the same base paste used in group I and a transparent catalyst were proportionally mixed for 20 seconds and then applied to the veneers. The specimens were light‐cured for 60 seconds each and were next subjected to AAA. They were submitted to color readings with a spectrophotometer in three instances: in the tooth surface (only the substrate), after the cementation and polymerization of the veneers, and after the AAA. The values of L*, a*, and b* were obtained and the total color change was calculated (∆E*). Values obtained were subjected to statistical analysis, with a significance of 0.05. Results There were no significant differences between dual‐ and light‐cured modes considering ∆E*, L*, a*, and b* values obtained after aging (p > 0.05). Within the dual‐cured mode there were no significant differences in ∆E*, L*, a*, and b* values (p > 0.05). Conclusion No relevant differences were found between the two activation modes in color change. When submitted to aging, dual‐ and light‐cured modes of the resin cement showed visually perceptible (∆E* > 1.0) color changes; however, within the threshold of clinical acceptance (∆E* > 3.3).